2016
DOI: 10.1007/s10900-016-0252-0
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Health Needs of High-Risk Filipino Americans in the Greater Philadelphia Region

Abstract: Background Filipino Americans represent one of the largest and most diverse immigrant populations in the United States. It has been established that chronic diseases are a significant public health issue affecting this population. Methods We conducted a health needs assessment of two hundred Filipino Americans aged 18 years or older residing in the greater Philadelphia region. Study participants were recruited from eight Filipino community-based organizations in the region. Information about demographic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 24 publications
(35 reference statements)
3
32
0
Order By: Relevance
“…We also investigated whether there were subethnic differences in health behavior practice between Chinese and Filipino Americans with CMD. Overall, Filipino Americans were more likely to have CMD than Chinese Americans, which is consistent with current literature ( Maxwell et al, 2012 ; Wang et al, 2011 ; Ye et al, 2009 ) and our previous study ( Bhimla et al, 2017 ). Given that age ( Fulop et al, 2010 ) and acculturation ( Koya & Egede, 2007 ; Teppala et al, 2010 ) have been reported to be related to increased risk of chronic diseases, the higher prevalence of CMD in Filipinos in our study may be attributed to the fact that our Filipino sample was significantly older and more acculturated than the Chinese sample.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also investigated whether there were subethnic differences in health behavior practice between Chinese and Filipino Americans with CMD. Overall, Filipino Americans were more likely to have CMD than Chinese Americans, which is consistent with current literature ( Maxwell et al, 2012 ; Wang et al, 2011 ; Ye et al, 2009 ) and our previous study ( Bhimla et al, 2017 ). Given that age ( Fulop et al, 2010 ) and acculturation ( Koya & Egede, 2007 ; Teppala et al, 2010 ) have been reported to be related to increased risk of chronic diseases, the higher prevalence of CMD in Filipinos in our study may be attributed to the fact that our Filipino sample was significantly older and more acculturated than the Chinese sample.…”
Section: Discussionsupporting
confidence: 92%
“…Logistic regression was used to determine which health behaviors were associated with 1) CMD status in Chinese and Filipino Americans separately, and 2) ethnicity among the individuals with CMD, controlling for demographics and acculturation variables. The demographic and acculturation variables found to be associated with CMD in previous studies ( Bhimla et al, 2017 ; Fulop et al, 2010 ; Koya & Egede, 2007 ; Teppala et al, 2010 ) (i.e., age, gender, marital status, education, income, and year in the US) were included as covariates in logistic regression analyses. Because a small number of frequency count in some cells were noticed, we used penalized logistic regression method, instead of maximum-likelihood estimation method, to reduce the bias resulting from the presence of small sample cells.…”
Section: Methodsmentioning
confidence: 99%
“…The limited number of available studies specifically focusing on Filipino American populations suggests that their overall health outcomes are worse compared with other racial groups and Asian American subgroups. 2 , 10 , 11 A recent study examining hypertension among Filipino Americans in Greater Philadelphia reported rates as high as 67.5%. 10 Another study from Las Vegas identified acculturation as a predictor of body–mass index (BMI), wait circumference, and waist–hip ratio among Filipino Americans with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Filipinos represent the second largest Asian immigrant population in the US, yet the behaviors affecting PA among this population are largely understudied [17]. Studies that assessed general PA levels among Filipinos in the northeast US found rates of participation to be lower than the national average [8,18]. In a recent study among Asian American subgroups in California, middle-aged (45-64 years) Filipinos had the lowest odds of meeting the American College of Sport Medicine's (ACSM) PA recommendations compared to other ethnic groups, including Chinese, South Asian, Japanese, Korean and Vietnamese [15].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that 30.6% of females and 46.1% of males were overweight, and 6% and 15.8% of females and males were obese, respectively, within the Filipino community in New Jersey [22]. Recent data have also indicated that 53% and 67.5% have been diagnosed with hypertension within the Filipino communities of greater New York City and Philadelphia regions [18,23]. Furthermore, Filipino Americans are at a higher risk for coronary heart disease compared to other Asian American groups [24,25,26].…”
mentioning
confidence: 99%